2019
DOI: 10.1111/jcpp.13142
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of psychological interventions for children and young people with post‐traumatic stress disorder

Abstract: Background: PTSD in youth may lead to long-lasting psychological implications, educational difficulties and increased healthcare costs. Psychological interventions have been shown to be effective in its management. The objective of this study was to assess the cost-effectiveness of a range of psychological interventions for children and young people with PTSD. Methods: A decision-analytic model was constructed to compare costs and qualityadjusted life years (QALYs) of 10 psychological interventions and no trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…On the other hand, an economic evaluation of psychological interventions for PTSD in children and young people, which also used efficacy data derived from a NMA and adopted a similar approach and methodology to the analysis described here, concluded that individual forms of TF-CBT were most cost-effective in the treatment of children and young people with PTSD, whereas EMDR occupied middle cost-effectiveness rankings amongst the treatment options assessed [39]. This finding was attributed to the lower effectiveness of EMDR relative to other treatments in children and young people compared with adult populations [40].…”
Section: Comparison With Existing Economic Evidencementioning
confidence: 86%
“…On the other hand, an economic evaluation of psychological interventions for PTSD in children and young people, which also used efficacy data derived from a NMA and adopted a similar approach and methodology to the analysis described here, concluded that individual forms of TF-CBT were most cost-effective in the treatment of children and young people with PTSD, whereas EMDR occupied middle cost-effectiveness rankings amongst the treatment options assessed [39]. This finding was attributed to the lower effectiveness of EMDR relative to other treatments in children and young people compared with adult populations [40].…”
Section: Comparison With Existing Economic Evidencementioning
confidence: 86%
“…To our knowledge, this is the first known NMA of treatments for children and young people with PTSD that was designed to inform a clinical guideline. The NMAs that utilised PTSD symptom change scores further informed the guideline economic analysis, described in a companion paper (Mavranezouli et al., accepted). NMA techniques enabled evidence synthesis from both direct and indirect comparisons between interventions, and allowed simultaneous inference on all treatments examined in pairwise trial comparisons while respecting randomisation (Caldwell et al., ; Lu & Ades, ).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic narrative reviews, meta-analyses, and randomized studies [30,[41][42][43][44][45] form a solid base in promoting EMDR therapy and its efficacy to reduce the characteristic symptoms of PTSD in adult, adolescent, and child samples. Usually, the standard protocol is modified to make the treatment easier and more acceptable for children and adolescents with the addition of particular strategies [44] or tools [33].…”
Section: Emdr Therapy In Children and Adolescentsmentioning
confidence: 99%